Optimalisasi Pelayanan Sekolah Minggu di GBI City Harvest Sakinah Melalui Penguatan Dasar Iman, Metode Pengajaran Interaktif, Teknologi Digital, dan Pelatihan Worship Leader - Waruwu, Nofedin; Ringo, Samuel Siringo; Dona, Endrow; Mawuntu, Shekinah Glory; Sitanggang, Martauli D. Rahayu; Mara, Djeta; Ohoiwutun, Karen Tifani; Hia, Tri Juliani (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Sunday School ministry plays an important role in the formation of children's faith and character. However, at GBI City Harvest Sakinah, this ministry faces obstacles of conventional methods, lack of technology integration, and lack of Worship Leader (WL) training. This Community Service activity aims to optimize Sunday School services through strengthening the basis of Bible-based faith, developing interactive methods, utilizing digital technology, and training WLs. The activity methods included training, workshops, and simulations, with 30 participants of teachers and children's ministry administrators. Evaluation results showed an increase in theological understanding, teaching skills, and children's enthusiasm in worship. The average participant satisfaction with the activity reached 93%. This activity is expected to become a contextual and adaptive model of children's ministry in the digital era.ABSTRAKPelayanan Sekolah Minggu berperan penting dalam pembentukan iman dan karakter anak. Namun, di GBI City Harvest Sakinah, pelayanan ini menghadapi kendala metode konvensional, kurangnya integrasi teknologi, dan minimnya pelatihan Worship Leader (WL). Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk mengoptimalkan pelayanan Sekolah Minggu melalui penguatan dasar iman berbasis Alkitab, pengembangan metode interaktif, pemanfaatan teknologi digital, dan pelatihan WL. Metode kegiatan mencakup pelatihan, workshop, dan simulasi, dengan 30 peserta guru dan pengurus pelayanan anak. Hasil evaluasi menunjukkan peningkatan pemahaman teologi, keterampilan pengajaran, dan antusiasme anak dalam beribadah. Rata-rata kepuasan peserta terhadap kegiatan mencapai 93%. Kegiatan ini diharapkan menjadi model pelayanan anak yang kontekstual dan adaptif di era digital.